2015
DOI: 10.3390/ma8115408
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Mechanical and Thermal Properties of Cement Board with Expanded Perlite Based Composite Phase Change Material for Improving Buildings Thermal Behavior

Abstract: Here we demonstrate the mechanical properties, thermal conductivity, and thermal energy storage performance of construction elements made of cement and form-stable PCM-Rubitherm® RT 28 HC (RT28)/expanded perlite (EP) composite phase change materials (PCMs). The composite PCMs were prepared by adsorbing RT28 into the pores of EP, in which the mass fraction of RT28 should be limited to be no more than 40 wt %. The adsorbed RT28 is observed to be uniformly confined into the pores of EP. The phase change temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…It can be observed that the difference of temperature amplitude between the enclosed part (right side) and imposed heating load (left side), for case without PCM was of 3°C, whereas the cases with 10% PCMs, 20%PCM and 30%PCM were associated to smaller internal temperature difference amplitudes of 3.3°C, 3.5°C and 4°C. These internal temperature differences at laboratory scale are consistent with the concept of improved heat capacity of the PCM mortars which, in turn, is in line with other studies [33]. The time delay between the maximum temperatures registered at the left side and right side for the case with 30% PCM was of nearly 3 min, in opposition to a smaller delay of 2.7 min (for the case with 20% PCM), 2.5 min (for the case with 20% PCM) and smaller delay associated to the case without PCM (1.5 min).…”
Section: Temperature Monitoring Of the Pilot Prototypessupporting
confidence: 92%
See 1 more Smart Citation
“…It can be observed that the difference of temperature amplitude between the enclosed part (right side) and imposed heating load (left side), for case without PCM was of 3°C, whereas the cases with 10% PCMs, 20%PCM and 30%PCM were associated to smaller internal temperature difference amplitudes of 3.3°C, 3.5°C and 4°C. These internal temperature differences at laboratory scale are consistent with the concept of improved heat capacity of the PCM mortars which, in turn, is in line with other studies [33]. The time delay between the maximum temperatures registered at the left side and right side for the case with 30% PCM was of nearly 3 min, in opposition to a smaller delay of 2.7 min (for the case with 20% PCM), 2.5 min (for the case with 20% PCM) and smaller delay associated to the case without PCM (1.5 min).…”
Section: Temperature Monitoring Of the Pilot Prototypessupporting
confidence: 92%
“…The results suggested that the PCM peak temperature shifts in the direction of the imposed flux, thus showing higher peaks for mortars with high PCM percentage. This trend has also been reported by others [27,33] and it can be explained by the increase in specific heat capacity. The representation of peak temperatures and the percentage of PCM in the mortars was made with two dashed lines that showed a clear linear relationship between them for both heating and cooling processes.…”
Section: Densitysupporting
confidence: 88%
“…Obtaining the polymeric membrane can be accomplished by applying various micro and macro-encapsulation techniques such as immersion and direct incorporation. Thus, in order to avoid the occurrence of the leakage of phase change material, it is necessary to create a membrane with a higher melting temperature than the material with phase change, and to add certain compounds that allow the increasing viscosity of the PCM [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Expanded perlite (EP) is an amorphous glassy volcanic rock and having porous structure. Because it has very low thermal conductivity (0.03 -0.05W/m°C), low sound transition property and nonflammability it is generally used as insulation material in buildings (9,10). Also, some researchers reported that, EP have a good supporting matrix for preparing composite PCMs.…”
Section: Introductionmentioning
confidence: 99%